TRANSMUCOSAL BUCCAL PATCHES CARRYING BENIDIPINE HYDROCHLORIDE WITH A UNIDIRECTIONAL RELEASE OPTIMIZED BY CENTRAL COMPOSITE DESIGN - SAMANTHULA, KUMARA SWAMY; THALLURI, CHANDRASHEKAR; OBBALAREDDY, SATYA; KOTHAPALLY, DANIEL; PAREPALLI, SRIKANTH (International Journal of Applied Pharmaceutics, 2025)
Objective: This investigation aimed to develop buccal patches of benidipine hydrochloride (BH) that provide unidirectional release and adhere well to the mucous membranes. Methods: The buccal patches of BH with a unidirectional drug release were made utilizing the solvent casting process using hydroxy propyl methyl cellulose, eudragit RL 100, and polyvinylpyrrolidone. The patches' water-resistant backing layer allowed for the controlled delivery of medication in one direction. Thickness, mass, surface pH, folding endurance, moisture absorption, in vitro release, ex-vivo permeation release, and accelerated stability experiments were all used to assess them. Results: Based on the optimized formulation, the moisture absorption percentage is 40.50±1.39%, whereas the range for the original formulation was 32.18±1.69% to 44.95±1.52%. According to the in vitro drug release assays, formulation F9 was able to release 99.86±1.39% of the medication until 6 h. The study found progressive and constant drug penetration, with 69.53±1.86 compared to 54.88±1.39% in 6 h from the improved formulation. Conclusion: A possible alternative drug delivery strategy for the systemic distribution of BH was suggested by the manufactured unidirectional buccal patches of BH, which released the maximal amount of medication during the prescribed mucoadhesion duration.